CD11c regulates late-stage T cell development in the thymus - Hou, Lifei; Yuki, Koichi (Frontiers in Immunology, 2022)
CD11c, also named integrin X, has been deemed solely as a dendritic cell marker for decades while the delineation of its biological function was limited. In the current study, we observed in mice that CD11c deficiency led to a defect in T cell development, demonstrated by the loss of CD4+CD8+ double positive (DP) T cells, CD4+CD8-, and CD4-CD8+ single positive (SP) T cells in the thymus and less mature T cells in the periphery. By using bone marrow chimera, we confirmed that CD11c regulated T cell development in the thymus. We further showed that CD11c deficiency led to an accelerated apoptosis of CD3 positive thymocytes, but not CD4-CD8- double negative (DN) T cells. Overall, this study added one more layer of knowledge on the regulatory mechanism of late-stage T cell development that the presence of CD11c in the thymus is critical for maintaining T cell survival.